Analysing low speed efficiency of switched reluctance motor material grade for electric vehicle. (2022) - Deepak, M.; Janaki, G.; Bharatiraja, C.
Abstract: The growth of Electric Vehicles (EVs) moving towards to environmental health, safety and sustainability in the world. The main subsystem of EVs is battery and motor. The high cost and minimum life duration of EVs mainly depend on an electric motor. At present EVs motor use high-cost rare earth, materials like Neodymium, Dysprosium, and samarium in PMSM and BLDC motors which have demagnetization problems. The induction motor materials produce high copper loss and reduce efficiency. The speed-torque characteristics of magnet-less low-cost silicon material Switched Reluctance Motor (SRM) is well suited for EV. Associated with other electrical machines, the SRM has high efficiency at high speed, high fault-tolerant and durability. This paper proposes a rating of 2 kW, 750 rpm and 8/6 topology to design a proficient SRM drive. The design has been carried out on EV using grade modelling with different high core silicon materials. The finite element analysis using Ansys software was done, for the different electrical steel materials performance analysis of magnetic flux density, developed power, rated torque, efficiency at rated speed and moving torque. The results are compared and analysed to select the silicon material accuracy for EV-SRM to optimize the design to increase efficiency at low speed.